Understanding the perceived role of mobile media in relation to development in a South African rural area - Chatikobo, Tatenda (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2019)
This study explores the different perceptions of mobile media in relation to development within Dwesa, a marginalised rural community in South Africa. The proliferation of mobile phones and increasing access to the internet in Africa, and South Africa in particular, is extensively documented and attempts have been made to explore its impact on development. Drawing on adapted aspects of the Diffusion of innovation theory (DoI), the study seeks to understand the relative advantage, compatibility with needs and values, and observable benefits of using mobile media for a rural community. I provide a critical discussion of the concept of development and its relationship with digital technologies and innovation. I reflect on the Diffusion of innovation theory, highlighting its critiques, adaptations and modifications in studies, particularly in the Global South. The present study employs a qualitative methodology and relies on focus groups, semi-structured interviews and observation as methods of data collection. Participants were divided into three focus groups based on Rogers classification of innovativeness (early adopters, majority adopters and late/non-adopters) and I conducted two follow-up interviews with participants of each focus group. I analysed the data thematically. Research participants identified several areas where mobile media contributed to development and positive change, such as lowering the cost of access to information and communication, staying in touch with distant relatives, increasing access to services and providing entertainment, especially among young people. The participants noted that despite these positive changes, that mobile media on its own cannot be expected to address challenges of infrastructure and public service delivery. Research findings also revealed that mobile media might interfere with socio-cultural values of respect, human dignity and privacy. I conclude that, while mobile media is generally considered as beneficial, its critical role in improving the socio-economic conditions of people in Dwesa still remains in doubt. The study provides an opportunity to further investigate the compatibility of mobile media with socio-cultural values along the lines of age and gender, and address issues of digital skills and digital marginalisation.
Keywords: Mobile communication systems -- South Africa; Internet telephony -- South Africa; Mobile communication systems -- Social aspects -- South Africa; Internet telephony -- Social aspects --South Africa